Innovations in kidney stone management: mini-PCNL for staghorn calculi in resource-limited settings - Nguyen, An Minh; Do, Hung Hai; Van Nguyen, Duc; Vo, Long Hoang (Frontiers in Urology, 2025)
IntroductionThis study evaluates our initial experience with miniaturized percutaneous nephrolithotomy (mini-PCNL) in Vietnamese patients with staghorn calculi, using an 18F metal access sheath. This technique addresses the challenges of complex kidney stone management in resource-limited settings.MethodsA multi-center retrospective review of 236 patients with staghorn calculi who underwent mini-PCNL with high-power Ho laser lithotripsy (Lumenis 100 W) was conducted at four provincial hospitals in northern Vietnam from January 2020 to December 2023.ResultsAmong the 236 patients (mean age 54.88 years), 13.56% had prior open surgery, and 3.81% had previous PCNL. Presenting symptoms included flank/back pain (97.88%), acute renal colic (11.44%), and dysuria (5.93%). Right-sided stones were present in 55.93%, left-sided in 32.63%, and bilateral in 11.44%. The mean stone size was 28.05 mm, with 53.81% having stones of 20–30 mm, 38.56% over 30 mm, and 7.63% under 20 mm. Single stones were noted in 69.07%, while 30.93% had multiple stones. The mean stone surface area was 318.17 mm². Hydronephrosis was observed in 53.81% (grade-1: 32.64%; grade-2: 17.37%; grade-3: 3.81%). Postoperative complications included bleeding (13.14%), fever (9.75%), and reoperation or JJ stent placement (1.69%). Stone clearance rates were 67.37% at three days and 80.91% after one month. The mean durations for ureteral catheterization, postoperative hospitalization, and total hospital stay were 3.29, 6.94, and 12.90 days, respectively.ConclusionsMini-PCNL with high-power Ho laser lithotripsy demonstrates safety and efficacy in managing staghorn calculi, achieving favorable stone clearance and recovery outcomes. This approach offers a viable, cost-effective solution for enhancing access to advanced urological care in resource-constrained environments.